Influence of flow direction and turbulence intensity on heat transfer of utility-scale photovoltaic solar farms. (1st September 2020) - Glick, Andrew; Smith, Sarah E.; Ali, Naseem; Bossuyt, Juliaan; Recktenwald, Gerald; Calaf, Marc; Cal, Raúl Bayoán
Highlights: First experiment considering a model solar farm. First experimental platform developed for scaled solar photovoltaics (PV). The impact of inflow condition and flow direction are tested. Results suggest that PV models could improve efficiency and power generation. Abstract: High operation temperatures in photovolatics (PV) strongly reduce efficiency, reduce panel lifetime, and negatively influence the cost of energy. Here, the convective heat transfer coefficient for a utility-scale solar farm is studied with combined thermal and particle-image-velocimetry measurements in a scaled wind tunnel experiment. Two key factors that have critical roles in modifying the overall efficiency, the turbulent inflow condition and the panel configuration, are investigated. The combination of Reynolds shear stress and buoyancy causes upward flow entrainment, increases the mixing mechanisms and the Nusselt number. Results show how variations in the turbulent inflow can increase the convective heat transfer by at least 7%. Further, increasing the panels inclination angle enhances convection up to an angle of approximately 30°, with more substantial increases measured when the mean flow approaches the solar array from the back.